Transmission of onchocerciasis by Simulium Sanctipauli ‘Pra’ form in the Upper Denkyira District, Ghana after Mass Ivermectin Treatment - Kutin, Richard Kwesi (2011)
A thesis Submitted to the Department of Clinical Microbiology, School of Medical Sciences, Kwame Nkrumah University of Science and Technology, Kumasi, for the award of the degree of M.Phil. in Clinical Microbiology.